Application of Two-Stage Data Envelopment Analysis (DEA) in Identifying the Technical Efficiency and Determinants in the Plastic Manufacturing Industry in Malaysia - Muhamad Azhar Nor Sabli; Mohd Fahmy Abdullah; Lai Wei Sieng (International Journal of Supply Chain Management, 2019)
This aim of this study is to measure the technical efficiency score and identify the factors that affect the technical efficiency in plastic manufacturing firm in Malaysia for the year 2015 using the two stage Data Envelopment Analysis (DEA) method. The first stage involves calculating the efficiency score through the DEA using firm-level data, provided by the Department of Statistics, Malaysia. In the second stage, Tobit Regression Analysis was used to identify the significant factors affecting the efficiency of the plastic industry. The determining factors are the labor-ratio, training expenses, educational level ratios, wage rates, information and communications technology expenses and firm size. The results show that average efficiency score is moderate rate. Information and communication technology (ICT) expenditure, wage rate, research and development expenditure and education level are significant factors of the efficiency factor of a plastic product manufacturing firm. The implication of this decision suggests that firms need to emphasize significant factors to enhance firms' efficiency.